Medieval Punctuation, mise en texte and the Digital World. - WARD, AENGUS (Bulletin of Hispanic Studies (1475-3839), 2020)
Studies of medieval histories tend to concentrate almost exclusively on the discursive content of manuscript text to the exclusion of the effect on the reader of the physical disposition on the page. The article takes advantage of recent digital advances to analyse material aspects of the Alfonsine Estoria de Espanna manuscripts, and proposes that questions of mise en page and mise en texte were central elements of the Alfonsine approach to the organization of knowledge.